Bar el Chino - Burak, Daniel; Levit, Mario Ezequiel; Lion, Mario; Latorre, Jimena; Dioguardi, Pasta; Sanchez, Nestor; Santa Ana, Lucas; Larrese, Ernesto (Buenos Aires Vocacion S.R.L., 2003)
Two filmmakers fall in love with each other and with Bar "El Chino", where tango is sung. Captivated, they work together on a documentary project about the Bar in an effort to capture the magic and essence of the place.
Published in association with Adart Producciones and the Instituto Nacional de Cine y Artes Audiovisuales.
Executive producer: Mario Ezequiel Levit ; Producer: Mario Lion.
Cast: Boy Olmi, Jimena La Torre, Pasta Dioguardi, Nestor Sanchez, Lucas Santa Ana, Ernesto Larrese.
Keywords: Bars (Drinking establishments) -- Drama; Man-woman relationships -- Drama; Feature films -- Argentina; Romance films; Comedy films